Anticonvulsant effect of Sphaeranthus flower extracts in mice - Apurva P. Dighe; Kalyani H. Barve (Journal of Ayurveda and Integrative Medicine, 2019)
Sphaeranthus indicus whole herb is included as a Rasayana drug in Ayurveda and is reported for the treatment of epilepsy. S. indicus flowers have anxiolytic, hypotensive, peripheral vasodilatory and cathartic activity. The objective of this study was to evaluate the anticonvulsant activity of the extract of flowers of S. indicus in various animal models of epilepsy. The anti-epileptic activity of Methanolic extract (ME) and Acetone extract (AE) of the flowers was evaluated using Maximal electro shock (MES) seizures, Pentyelenetetrazole (PTZ) induced convulsions and Picrotoxin induced convulsions. ME (50 mg/kg and 100 mg/kg) and AE (100 and 200 mg/kg respectively) protected animals against PTZ and Picrotoxin induced convulsion but did not have any effect against MES induced convulsion. In conclusion, the results of this study suggest that both the ME and AE possess promising anticonvulsant activity. It is further suggested that the flavonoids in the extract by the virtue of their effect on benzodiazepine site of GABA receptor, might be responsible for the effect, although no study is undertaken to prove this aspect. Nevertheless, the study provides pharmacological credibility to the anti-epileptic use of S. indicus suggested in Ayurveda.